PEMERATAAN PEMBANGUNAN MELALUI KEBIJAKAN PEMEKARAN WILAYAH - Dellia Ayu Nurparikha; Endah Mustika Ramdani; Achmad Sodik Sudrajat; Alikha Novira (Jurnal Kebijakan Publik, 2023)
This research examines the implementation of the CDPOB regional expansion policy in South Garut Regency, focusing on policy implementation in accordance with Undang-Undang Nomor 23 Tahun 2014 on Regional Government and the bottom-up method. This research uses a descriptive qualitative approach involving interviews with stakeholders at the Provincial level and documentation studies, to analyze the success of the policy. This research uses Richard Matland's policy implementation theory which includes five dimensions, namely policy accuracy, implementation accuracy, target accuracy, environmental accuracy, and process accuracy. The results showed that the implementation of the CDPOB regional expansion policy for South Garut Regency as a whole has been running in accordance with the rules. However, the implementation has not been completely perfect even though it has fulfilled Richard Matland's five indicators. There are also obstacles in the implementation of the CDPOB expansion policy of South Garut Regency, including the feasibility assessment that has not reached the minimum requirements in the Draft Government Regulation (RPP) on Regional Arrangement, improvement notes, and community conflicts even though they have been resolved. In terms of assessment, further analysis and programs are needed to improve the low sub-indicator scores.